The association of race with quality of health in peripheral artery disease following peripheral vascular intervention: The Q-PAD Study. (December 2017) - Zaitoun, Anwar; Al-Najafi, Saif; Musa, Thaer; Szpunar, Susan; Light, Dawn; Lalonde, Thomas; Yamasaki, Hiroshi; Mehta, Rajendra H; Rosman, Howard S
Black patients have a higher prevalence of peripheral artery disease (PAD) than white patients, and also tend to have a greater extent and severity of disease, and poorer outcomes. The association of race with quality of health (QOH) after peripheral vascular intervention (PVI), however, is less well-known. In our study, we hypothesized that after PVI, black patients experience worse QOH than white patients. We retrospectively assessed racial differences in health status using responses to the Peripheral Arterial Questionnaire (PAQ) at baseline (pre-PVI) and up to 6 months following PVI among 387 patients. We used the PAQ summary score (which includes physical limitation, symptoms, social function and quality of life) as a measure of QOH. We compared QOH scores at baseline and at follow-up after PVI between black ( n =132, 34.1%) and white ( n =255, 65.9%) patients. We then computed the change in score from baseline to follow-up for each patient (the delta) and compared the median delta between the two groups. Multivariable regression was used to model the delta QOH after controlling for factors associated with race or with the delta QOH. There was no significant difference in mean QOH by race either at baseline ( p =0.09) or at follow-up ( p =0.45). There was no significant difference in the unadjusted median delta by race (white 25.3 vs black 21.5, p =0.28) and QOH scores improved significantly at follow-up in both groups, albeit the improvement was marginally lower in black compared with white patients after adjustment for baseline confounders ( b = −6.6, p =0.05, 95% CI −13.2, −0.11).